Functional Model of Psychological Service in the Education System: Areas of Activity and Its Organizational and Legal Regulation - O.A. Ulyanina; O.L. Yurchuk; Yu.V. Tukfeeva; N.N. Filatova; I.D. Ryzhova (Психолого-педагогические исследования)
The article presents the results of a monitoring study of the functional model of psychological service in the system of general education and secondary vocational education. The purpose of the monitoring is to study variable approaches to the implementation of psychological and pedagogical support in various regions of the Russian Federation. The study was conducted from March to April 2024 in 8 constituent entities of the Russian Federation, and involved educational psychologists (educational psychologists) from preschool, general education and professional educational organizations. The total sample size was 2288 people. The article discusses the analysis of the results obtained in accordance with the identified functional blocks: organizational and legal regulation of psychological and pedagogical support activities and areas of activity of psychological services in the system of general education and secondary vocational education. The study made it possible to comprehensively present the current state of the psychological service, its development resources and areas of improvement. This study will become the basis for further development of a draft functional model of psychological service in the system of general education and secondary vocational education, as well as variable models of its organization.